Myositis and immune reconstitution inflammatory syndrome in an immuno compromised patient: A therapeutic conundrum - Chatterjee, Nandini; Pain, Shantasil; Banerjee, Abhirup; Patary, Brikodar; Ghatak, Souvik (Indian Journal of Case Reports, 2019)
Microsporidia are ubiquitous fungi that may infect animals, fish, insects as well as humans. Human infection is uncommon and only seen in the immunocompromised individual. Here, we report the case of a 40-year-old known AIDS patient presented with severe myalgia and inability to walk. Investigations revealed microsporidial myositis. Her treatment was further complicated by the development of acute inflammatory demyelinating polyneuropathy (AIDP) 2 weeks later. However, treating human immunodeficiency virus, microsporidiosis, and AIDP as a consequence of immune reconstitution inflammatory syndromeconcomitantly led to clinical improvement.